Formula Optimization of Annona muricata Folium Ethanolic Extract of Anti Acne Gel Formulation using Factorial Design Method - Aristha Novyra Putri; Noor Laila; Dyera Forestryana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Acne is a pile of oil glands in the skin that are actively being clogged by dirt and infection because of Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. The treatment for acne can use herbal ingredients, one of which is Soursop (Annona muricata L.) leaves ethanolic extract. Annona muricata folium ethanolic extract is known to have alkaloid, flavonoid and polyphenol compounds which can inhibit the growth of P. acnes, S. epidermidis, and S. aureus. Suitable dosage forms for anti-acne preparations are gels because the gel contains much water so that it provides a cooling effect on the skin due to inflammation. The purpose of this study was to determine the impact of carbopol 940 and Propylene glycol on the physical characteristics of the gel preparation and determine the optimum formula of the gel preparation using factorial design software 22 so that the gel preparation was made in four formulas. The data obtained were then analyzed using Design-Expert® and ANOVA software with a confidence level of 95%, and the determination of the optimum formula based on the optimum superimposed contour plot area. The results of the study using a factorial design approach are known that Propylene glycol has an effect on increasing the spreadability and pH while carbopol 940 has a more significant impact on the increase in adhesion and viscosity, and the optimum area of ​​the composition of carbopol 940 1.536% and propylene glycol 5% was obtained.